2004
DOI: 10.1038/sj.bjc.6602093
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two contiguous minimally deleted regions on chromosome 1p36.31–p36.32 in oligodendroglial tumours

Abstract: Loss of the short arm of chromosome 1 is a hallmark of oligodendroglial tumours (OTs). Deletion mapping studies in OTs have revealed multiple commonly deleted regions on chromosome 1p, suggesting that there are more than one tumour suppressor gene. To map critical deletion regions on 1p, a series of 25 OTs were examined for loss of heterozygosity (LOH) on 19 polymorphic markers across the 1p arm using microsatellite analysis. Our study revealed that 60% of tumours had LOH of all informative markers on 1p and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
4
32
0
1
Order By: Relevance
“…14 It should be noted that during the course of our study, a nearly identical consensus region of deletion was identified in an independent study of 52 oligodendroglial tumors, with SHREW1 as the only gene in the consensus region. 15 SHREW1 encodes a novel transmembrane protein in adherens junctions. 16 The loss of adherens junctions has been shown to promote tumor cell infiltration and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…14 It should be noted that during the course of our study, a nearly identical consensus region of deletion was identified in an independent study of 52 oligodendroglial tumors, with SHREW1 as the only gene in the consensus region. 15 SHREW1 encodes a novel transmembrane protein in adherens junctions. 16 The loss of adherens junctions has been shown to promote tumor cell infiltration and metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…20 In brief, 5-mm thick formalin-fixed, paraffin-embedded sections were deparaffinized in xylene, treated with 1 M sodium thiocyanate at 80 1C for 10 min, digested in pepsin solution at 37 1C for 20-30 min, rinsed in milli-Q water and dehydrated. Locus-specific probes were generated from bacterial artificial chromosome clones using nick translation, in the presence of Spectrum Orange deoxyuridine triphosphate (dUTP) …”
Section: Chromosome 1p/19q Status By Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…In line with this conjecture, the genomic region 1p36, encompassing the miR-34a gene, is frequently deleted in a variety of human cancers. 48,53,54 Welch et al reported that the miRNA-34a gene is hemizygously deleted in approximately 30% of advanced stage neuroblastomas and that mature miR-34a is under-expressed in primary neuroblastoma tumors and cell lines. 48 Furthermore, ectopic overexpression of miR-34a induced growth arrest and apoptosis in neuroblastoma-derived cells.…”
Section: Biology and Targets Of P53-regulated Mirnasmentioning
confidence: 99%